Benefits of β-hydroxy-β-methylbutyrate supplementation in trained and untrained individuals. Issue 2 (3rd April 2019) - Gepner, Yftach; Varanoske, Alyssa N.; Boffey, David; Hoffman, Jay R.
ABSTRACT: β-Hydroxy-β-Methylbutyrate (HMB) is a metabolite of the branched-chain amino acid leucine and its ketoacid α-ketoisocaproate. HMB has been widely used as an ergogenic supplement to increase muscle strength, muscle hypertrophy and enhance recovery. The physiological mechanisms that underlie these benefits are related to HMB's ability to stimulate muscle protein synthesis and minimize muscle breakdown. Although evidence supporting the benefits of HMB supplementation is not conclusive, many of these studies have suffered from methodological flaws including different formulations, supplement duration and population studied. HMB in its free acid formulation is suggestive of having a greater potential for efficacy in both trained and untrained populations than its calcium-salt form. However, the evidence regarding HMB's role in limiting muscle degradation and increasing muscle protein synthesis has created an exciting interest in examining its efficacy among untrained individuals. Recent investigations examining intense training have demonstrated efficacy in maintaining muscle mass and attenuating the inflammatory response.